Pyrene‐Fused Perylene Diimides: New Building Blocks to Construct Non‐Fullerene Acceptors With Extremely High Open‐Circuit Voltages up to 1.26 V. Issue 10 (18th September 2017) - Zhan, Xuejun; Xiong, Wentao; Gong, Yanbin; Liu, Tao; Xie, Yujun; Peng, Qian; Sun, Yanming; Li, Zhen
Abstract : Great efforts have been devoted to seeking alternative non‐fullerene acceptors for efficient polymer solar cells (PSCs). Achieving a high open‐circuit voltage ( V oc ) is quite challenging but is essential for practical application. Here, pyrene‐fused perylene diimide was first used as a periphery building block to construct non‐fullerene acceptors. Due to the high‐lying lowest unoccupied molecular orbitals (LUMOs) as well as balanced transport properties, the normal devices with the acceptors exhibited ultrahigh V oc values of up to 1.26 V. In addition, the achieved power‐conversion efficiency (PCE) of 5.10% is among the highest values for non‐fullerene PSCs with a V oc  > 1.20 V, indicating that the pyrene‐fused perylene diimide (PDI) unit is a useful building block for the design of non‐fullerene PSCs with high V oc values. This study could benefit the realization of both a high PCE and V oc in PSCs. Abstract : By fusing perylene diimides with pyrene, non‐fullerene acceptors with high‐lying lowest unoccupied molecular orbitals, as well as balanced transport properties, are successfully obtained. The fabricated polymer solar cells exhibit ultrahigh open‐circuit voltages of up to 1.26 V, with a small energy loss of 0.65 eV. This study provides a valuable guidance for the design of non‐fullerene acceptors.